ANALYSIS OF STUDENTS' NUMERATION SKILLS FOR LINEAR EQUATIONS MATERIAL BASED ON HONEY AND MUMFORD'S LEARNING STYLE - Krisyani Krisyani; Sri Hariyani; Vivi Suwanti (Program Studi Pendidikan Matematika, Universitas Bina Bangsa Getsempena, 2024)
The results of observations at SMP Negeri 02 Gondanglegi Class VII A showed that students were less precise in solving conceptual understanding questions. It can be seen that students cannot understand the changes in positive and negative signs when moving numbers in an equation, so this numeracy research is needed to identify students' difficulties. The focus of the research is to describe students'numeracy abilities based on Honey and Mumford's learning style in solving linear equation problems in class VII A of SMP Negeri 02 Gondanglegi. The research uses descriptive qualitative research. The subjects consisted of 4 students with the highest scores in different learning styles according to Honey and Mumford, namely: activists, reflectors, theorists, and pragmatists. Data collection procedures include questionnaires, tests, interviews, and documentation. Data is evaluated through a process of data reduction, data presentation, and drawing conclusions. Based on the analysis, students with a pragmatic learning style have better numeracy skills because the student's character is open, giving rise to great curiosity, trial and error, courage and creativity. Students with an activist learning style improve their numeracy skills when their numeracy skills increase along with their greater curiosity. Meanwhile, students with a reflector learning style have invisible numeracy abilities, and are even disturbed because they think randomly. Students with a theoretical learning style have high numeracy skills in the applying question type and dominate in the employ step according to routine training by the teacher. It was concluded that students with a pragmatic learning style had higher numeracy abilities, compared to students with an activist, reflector, or theoretical learning style. It is important that this research was carried out as a contribution to improving students' numeracy skills by using the Honey and Mumford learning style as a reference.